ANALISIS HUKUM PERLINDUNGAN KONSUMEN ATAS TRANSAKSI JUAL BELI MELALUI IKLAN FACEBOOK - Sri Agustini; Miasiratni Miasiratni; Widya Yoseva (Ensiklopedia of Journal, 2025)
Abstract: Social media platforms such as Facebook are now widely used as tools for product promotion and transactions. However, this transaction model often lacks adequate legal protection for consumers. This study aims to analyze the form of legal protection for consumers who purchase products through Facebook advertisements. The research method used is normative juridical, with a statutory and literature approach. The findings indicate that transactions through Facebook ads are generally conducted directly between sellers and buyers without third-party intermediaries, thereby increasing the risk of consumer loss—especially in cases of fraud, mismatched goods, or undelivered products. Law No. 8 of 1999 on Consumer Protection has not been fully effective in protecting consumers in such transactions, as it does not specifically regulate commercial activities on social media. Therefore, additional regulations are needed, along with efforts to improve public digital literacy so that consumers better understand their rights and avoid potential losses.Keywords: consumer protection, Facebook ads, online transactions.